The Role of Self Efficacy as a Mediating Variable in the Relationship between CareerEDGE Model and Employability of Economics Bachelor at Universitas Negeri Padang - Aziz, Muhammad; Andriani, Chichi (Human Resource Management Studies, 2023)
The objective of this research is to investigate the effects of the careerEDGE model (has variables; career development, experience, subject knowledge, skills, and comprehension, general skills, and emotional intelligence) on employment. Additionally, the role of self-efficacy in the relationship between careerEDGE and employability was examined. The population of this study was 649 undergraduate students from the 2019 Faculty of Economics, Universitas Negeri Padang. The method of sampling in this study was proportional random sampling with a total of 247 undergraduate students from the class of 2019, located at the faculty of economics, Universitas Negeri Padang. The analysis in this investigation utilizing software SmartPLS 4.0. The results of this investigation are; (1) career development learning has no significant effect on employability. (2) experience has no significant effect on employability; (3) degree subject knowledge, skills, and understanding significant effect on employability; (4) generic skills has no significant effect on employability; (5) emotional intelligence significant effect on employability; (6) self efficacy significant effect on employability; (7) career development learning significant effect on employability through self efficacy; (8) experience significant effect on employability through self efficacy; (9) degree subject knowledge, skills, and understanding significant effect on employability through self efficacy; (10) generic skills significant effect on employability through self efficacy. (11) Emotional Intelligence significant effect on employability through self efficacy.